1971
DOI: 10.1029/jc076i021p05117
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium of carbon monoxide and methane at the air-sea interface

Abstract: Supersaturation of carbon monoxide was found in the surface waters of the Pacific Ocean on a recent cruise to Hawaii, which confirmed previous findings in the Atlantic. A diurnal cycling effect was observed, with maximum production of CO occurring during daylight hours. When compared to measured atmospheric partial pressures of CO, the concentrations of dissolved CO were found to be 15 to 75 times higher than atmospheric equilibrium values. Measurements of methane made concurrently with those for carbon monoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 13 publications
2
23
1
Order By: Relevance
“…Results Table 2 indicate regions without data. Early measurements (late 1960s and early 1970s) in the Pacific by Lamontagne et al [1971Lamontagne et al [ , 1973Lamontagne et al [ , 1974 suggested that the ocean was much more supersaturated at that time with average SR of approximately 1.3. [1995] for the world's oceans.…”
Section: Apch4 = (Pa -Pw) [(X)w-(x)a]mentioning
confidence: 99%
“…Results Table 2 indicate regions without data. Early measurements (late 1960s and early 1970s) in the Pacific by Lamontagne et al [1971Lamontagne et al [ , 1973Lamontagne et al [ , 1974 suggested that the ocean was much more supersaturated at that time with average SR of approximately 1.3. [1995] for the world's oceans.…”
Section: Apch4 = (Pa -Pw) [(X)w-(x)a]mentioning
confidence: 99%
“…CH 4 is often 10 to 75% supersaturated within the oxygenated surface mixed layer in most areas of the global ocean (Lamontagne et al 1971(Lamontagne et al , 1973, making the oceans a net source of this gas to the atmosphere (Owens et al 1991, Bange et al 1994, Bates et al 1996, Rhee et al 2009. In the open ocean, these supersaturated concentrations are thought to be the product of in situ production in this oxygenated layer (Scranton & Brewer 1977, Tilbrook & Karl 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is the major substrate of the reactions of hydroxyl radical in the troposphere and hence strongly affects the oxidizing capacity of the atmosphere and the concentrations of other trace gases. Concentrations of CO dissolved in surface seawater are much higher than expected by equilibration with atmospheric CO 1–6. The supersaturation results in a flux of CO from the ocean into the atmosphere that has been estimated by several investigators to be in the order of 10–245 Tg/yr,5–7 suggesting its significant role in marine boundary chemistry.…”
mentioning
confidence: 95%